The Environmental Factor in the Ideological Debates Surrounding the Development of Latin America [el Factor Ambiental en Los Debates Ideológicos en Torno Al Desarrollo de América Latina] - Estenssoro-Saavedra, J (Universidade do Vale do Rio dos Sinos, 2017)
This article provides historical background on how the concept of development has played a key role in the political-ideological debate both in the international system as locally, from the end of Second World War on, particularly associated with the environmental debate since its beginning, as well as how it has been expressed this phenomenon in Latin America. It is noted that critical ideas to the concept of development are born within US neo-Malthusian elites and they simultaneously become a structural part of the ecological thought in the World War I. Finally, this study exposed how these ideas of criticism have been strengthened and how they have an interesting presence in the ideological debate in Latin America in the twenty-ffirst century.